(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The objective of this research project was to analyze the effects of the application of pregerminative stimulants and different types of substrates in the germination of Gmelina arborea, in the nursery stage. For the application of the project, 3.5 pounds of melina seeds were purchased to which the respective pregerminative treatment was applied, prior to the sowing of the same ones, establishing a total of 1,440 seeds in 36 tubes of 40 seeds per tube. With three repetitions, three pregerminative treatments were used (nitric acid and distilled water, hot water and cold water) on G. arborea Robx seeds, with three combined substrates (orchard soil + sand, common soil + UTEQ fertilizer, common soil + rice husk), plus the control to which no treatment was applied, since it served as a control, but it was sown on combined substrates. After two weeks of germination data collection, the growth variables were measured during 8 weeks of height, number of leaves, stem diameter, length and width of the leaf and length of the root, the latter only once. The work was carried out in the experimental farm "La Represa" owned by the State Technical University of Quevedo. The pregerminative treatments applied to Gmelina arborea Robx seeds, varied in differences on germination between treatments, in addition to the different combined substrates in which it was put to germinate, differences were evidenced in how many growth variables. Giving us as results several similarities between treatments and substrates.